2000
DOI: 10.1097/00005768-200008000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Influence of carbohydrate on cytokine and phagocytic responses to 2 h of rowing

Abstract: These data indicate that carbohydrate compared with placebo ingestion attenuated the moderate rise in blood neutrophils, monocytes, phagocytosis, and plasma IL-1ra concentrations that followed 2-h bouts of training in elite female rowers. No changes in blood hormone concentrations were found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
47
1
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 20 publications
7
47
1
2
Order By: Relevance
“…This discrepancy may relate to the lower intensity and duration of exercise in the present study compared with other studies, which have typically involved more intense (i.e., $70% VO2max) and/or prolonged exercise (i.e., $2 h) (1-3). In the present study, plasma glucose concentration at the end of exercise in the isotonic and hypotonic drink trials was similar to or higher than other studies on the effects of carbohydrate supplementation on immunoendocrine responses to exercise (3)(4)(5)(21)(22)(23)(24). Plasma glucose concentration at the end of exercise in the water trial in the present study was also higher than in some other studies (3,23,24).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This discrepancy may relate to the lower intensity and duration of exercise in the present study compared with other studies, which have typically involved more intense (i.e., $70% VO2max) and/or prolonged exercise (i.e., $2 h) (1-3). In the present study, plasma glucose concentration at the end of exercise in the isotonic and hypotonic drink trials was similar to or higher than other studies on the effects of carbohydrate supplementation on immunoendocrine responses to exercise (3)(4)(5)(21)(22)(23)(24). Plasma glucose concentration at the end of exercise in the water trial in the present study was also higher than in some other studies (3,23,24).…”
Section: Discussionsupporting
confidence: 82%
“…Some studies report that carbohydrate prevents a decline in neutrophil elastase release (3) and oxidative burst activity (25), whereas other studies demonstrate no effect of carbohydrate (2,(22)(23)(24)26). These discrepant findings are likely due to variation in various factors including exercise protocols, the training status of subjects, timing of blood samples and assays of neutrophil function (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…The systemic plasma concentration of IL-8 increases in response to exhaustive exercise such as running, which involves eccentric muscle contractions [203][204][205]. In contrast, concentric exercise such as bicycle ergometry [206] or rowing [207] of moderate intensity does not increase plasma IL-8 concentration. However, intense cycle ergometry has been reported to increase IL-8 plasma concentration to a small degree [208].…”
Section: Is the Muscle Il-6 Release A Metabolic-related Event?mentioning
confidence: 99%
“…Moreover, the study conducted by Nieman et al reported that blood concentration of myokines was increased after treadmill running for 3 hours at the 70% VO2max intensity, in 16 marathon runners [28]. However, moderate intensity exercise using cycle ergometer [29] and rowing [30] does not induce an increase in blood concentration. These results reflected that an increase of myokine concentration in blood is proportional to the type of exercise, the duration, intensity, and muscle mass [26,27].…”
Section: Discussionmentioning
confidence: 97%